Exploring the Impact of Teaching Communication in Chinese as a Foreign Language on the Perception of Chinese Corporate Image - Yongshuang Zhao; Jianli Wei; Aidah Binti Abdul Karim; Fariza Khalid; Mohd Khalid Bin Mohamad Nasir (Kurdish Studies, 2023)
Considering the social, emotional, environmental, physiological and psychological dimensions of Chinese language learners, we establish a label library of learning behaviors of Chinese as a foreign language, and propose a clustering algorithm of learning behaviors based on fuzzy C-means. Consistency reliability measures are determined through reliability analysis. Combined with structural equation modeling, 12 observational variables are established with knowledge base, cognitive ability and psychological characteristics as latent variables, and four hypotheses are proposed for the influence of Chinese as a foreign language teaching communication on the perception of Chinese corporate image. The results verify the validity of the model, and the non-assignment fit indices and comparative fit indices of knowledge base of Chinese as a foreign language, cognitive ability and psychological characteristics are all greater than 0.9, which show a significant positive effect of teaching communication in Chinese as a foreign language on the perception of Chinese corporate image.